Upaya Meningkatkan Hasil Belajar Matematika Siswa Kelas I Melalui Penerapan Metode Buzz Group Disertai Media Lidi Pada Materi Penjumlahan Bilangan Cacah Di SD Negeri 060886 Medan Tahun Ajaran 2018/2019 - Agustina Ginting (Universitas Islam Sumatera Utara, 2022)
This study aimed to find out how to improve learning outcomes of Mathematics toward the Addition to Whole Numbers through the Buzz Group method by using Stick media in the first grade students of SD Negeri 060886 Medan; and howÂ the creativity and ability of teachers in carrying out learning in the classroom. The proposed hypothesis is: How can the learning outcomes of mathematics in the Addition of whole numbers material can be improved through the Buzz Group method with Lidi media. This classroom action research was conducted in two cycles by using the application of the Buzz Group method proposed by Dimyati and Mudjiono.The results of the study concluded that student learning outcomes in learning through the application of the Buzz Group method were students' abilities with a completeness percentage as 17.39% in the cycle I with an average score as 5.69 and 86.95% with an average score as 8,52 in cycle II, and students are very motivated and enthusiastic and cheerful, then the Teaching and Learning Activities (KBM) has been applied in good results.Â